Vergewaltigung und sexuelle Nötigung Untersuchung der Strafverfahrenswirklichkeit - Goedelt, Katja (Universitätsverlag Göttingen, 2010)
Sexual violence attains a high level of public attention, almost daily the media report about it. Also for the crime and justice policy, it was always a reason to discuss the sharpening and expansion of sentences. More astonishing is that hardly anyone has examined why relatively many persons is suspected of sexual violence, but only a small percentage is ever sentenced. This volume is intended to provide new insights by describing on the one hand the identified issues, and on the other hand analysing identification processes, selection processes and sentencing. This will be based on a census of investigations in two court districts in Lower Saxony.